MALNUTRITION IN PATIENTS WITH COVID-19: SYSTEMATIC REVIEW - Novitarina, Elysabet (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Patients infected with severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), patients hospitalized for COVID-19, and patients recuperating (sometimes over several months) from the acute disease all display the same symptoms: exhaustion and a low functional level. The loss of muscle mass and cachexia, as well as the malnutrition and complex metabolic alterations that are frequently associated with these conditions, are thought to play a significant role in both the acute clinical problems and the long-term health damage caused by post-COVID-19 chronic disease. Patients with moderate COVID-19 who are treated at home are at a higher risk of malnutrition. Changes in smell and taste, as well as weariness and a lack of appetite, have been identified as very common symptoms in COVID-19 patients, which may reduce the amount of food ingested. Because to COVID-19 symptoms, patients may be restricted to their homes, limiting their physical activities. This can cause a loss of lean mass. Malnutrition may occur as a result of these reasons and a systemic inflammatory response in people who aren't being treated in hospitals.